Addendum: Measurement and QCD analysis of double-differential inclusive jet cross sections in proton-proton collisions at ?s=13 TeV - Tumasyan, A.; Adam, W.; Andrejkovic, J. W.; Bergauer, T.; Chatterjee, S.; Dragicevic, M.; Del Valle, A. Escalante (Springer, 2022)
The QCD analysis at NNLO is repeated by using the NNLO interpolation grids for the double-differential inclusive jet cross section [1], which were released after the journal publication of the original analysis. The NNLOJET calculation used to derive these grids is based on the leading-colour and leading-flavour-number approximation and does not include the most recent subleading colour contributions. However, these contributions were reported in ref. [2] to be very small in inclusive jet production, in particular for a jet size of R = 0.7. The grids also contain an estimate of the numerical integration uncertainty of around 1% or less. To account for point-to-point fluctuations, this uncertainty, after consultation with the authors of NNLOJET, has been increased by a factor of two; however, its impact in the fit is negligible. A comparison of the measurement with predictions using various PDFs is shown in figure 1. Although the PDF parametrisation remains identical, higher precision in PDF and QCD parameters is expected by using NNLO grids consistently in the QCD analysis. These new results supersede those obtained by using the k-factor technique.